Effects of Ascaridia galli Infection on Mucin-Producing Goblet Cells in the Mucosal Duodenum of Indonesian Local Chickens (Gallus domesticus) - Prastowo, J.; Ariyadi , B. (International Journal of Poultry Science, 2018)
Background and Objective: Chickens infected with Ascaridia galli worms (A. galli ) suffer from slow growth and decreased weight gain. Infection with A. galli usually causes severe damage to the intestines due to migration of the worms in the tissue phase of the intestinal mucosa layer, which affects the proliferation of goblet cells in the duodenums of affected chickens. It is necessary to conduct a study that evaluates the effects of A. galli infestation on the number of goblet cells in the duodenal epithelium of infected chickens. Methodology: In this study, we used a total of 20day-old chicks (DOC). The A. galli worms used in this study were obtained from local chicken slaughterhouses. The worm eggs were embryonized to the L2 stage and inoculated with as many as 5000 eggs/chicken. Samples of the duodenum were taken after the chickens were 6 weeks old, at which time Periodic Acid Schiff (PAS) staining was performed. The elimination rate of the number of worm eggs after the infection was observed every once a week up to week 6 of the research period. Results were analyzed using Student’s t-test and descriptive analysis. Results: There tended to be a higher number of mucin-producing goblet cells in the treatment group than in the control group. The number of worm eggs found increased until the 21st day after infection. The peak of worm egg elimination occurred on the 21st day after infection, with a mean of 2000±250 eggs per gram (EPG); however, the number decreased again on the 28th day after infection. Conclusion: Based on the results of this study, it can be concluded that A. galli infection has a significant effect (p<0.05) on the increased number of goblet cells in the duodenal epithelium of broiler chickens. This worm infection also affects the length of the duodenum and the increase in chicken body weight on a weekly basis.